Dopolnitel'noe professional'noe obrazovanie kak faktor razvitija psichologiceskogo zdorov'ja trenerskich kadrov - Kvashuk, P. V.; Voronov, A. V.; Semaeva, G. N.; Kostyukov, P. P.; Rusakov, Yu. V.; Chernyshov, M. Yu.; Burlevich, V. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The main factor limiting the achievement of a high sports result in BMX cycling is the level of the athlete's special strength preparedness, and the special working capacity is determined by the integration of the properties of the neuromuscular apparatus that generates the manifestation of strength, power, speed, when performing a competitive exercise. The paper presents the results of an experimental study aimed at identifying the features of the implementation of the special power qualities of BMX cyclists in the process of overcoming the competitive distance. It was established that for BMX cyclists of high qualification, in the phase of maximum increase in power, the average values of the moment of force were: 53,1 ± 8,7%, and in the phase of the maximum increase in cadence: 32,3 ± 3,6% of the maximum isometric strength of the muscle group m. quadriceps. In the group of BMX women cyclists with high qualifications, in the phase of maximum increase in power, the average values of the moment of force were: 46,7 ± 5,6%, and in the phase of the maximum increase in cadence: 32,2 ± 2,9% of the maximum isometric strength of the muscle group m. quadriceps.